The Types of the Hot-Dipped Galvalume Post-Treatment Film and the Control Technology of Film Forming Process - LIU Jin-hua, XU Yong (Cailiao Baohu, 2021)
The performance characteristics and product application scopes of five kinds of post-treatment films of the hot-dipped Galvalume line in Meigang cold rolling plant were summarized, and the type of post-treatment films was reasonably selected according to the user’s requirements and the products service environment to make the post-treatment films have application performance. The controlling points of the post-treatment process of the hot-dipped Galvalume line was focused on, so as to obtain uniform and stable film thickness. In particular, the improvement measures of surface defects-stains and missing coating defects were summarized to reduce quality loss and improve the comprehensive performance of the hot-dipped Galvalume products.